EPCO-13. MULTIOMIC SINGLE NUCLEUS RNA- AND ATACseq PROFILING REVEALS REGULATORS OF GLIOMA CELL STATE DIVERSITY. (12th November 2021) - Anderson, Kevin; Johnson, Kevin; Varn, Frederick; Bessonett, Shannon; Gujar, Amit; Flynn, Bill; Courtois, Elise; Hau, Ann-Christin; Golebiewska, Anna; Paek, Sun Ha; Niclou, Simone; Samuels, Michael; et al.
Abstract: Multiomic single nucleus RNA- and ATACseq profiling reveals regulators of glioma cell state diversity. The extensive intra- and intertumoral heterogeneity observed in glioma reflects the resistance to therapy and poor prognosis observed clinically. Single-cell sequencing studies have highlighted that glioma heterogeneity reflects the co-existence of cell subpopulations with distinct cell states. Prior studies have also shown that EGFR-amplifying extrachromosomal DNA (ecDNA) elements in IDH-wild-type gliomas can contribute to heterogeneity by driving oncogene amplification through long range chromatin contacts. However, single cell studies have largely focused on analyses of transcriptional profiles, and the epigenetic mechanisms underlying the contribution of ecDNA elements to tumor cell state diversity remain poorly understood. To further our understanding of the regulatory programs that contribute to transcriptional diversity and mediate the distribution of tumor cell states, we profiled primary-recurrent tumor pairs from 18 patient samples with multiomic single-nucleus RNA- and ATACseq, resulting in 86, 135 cells identified with linked chromatin accessibility and gene expression profiles. Integrative clustering of the tumor cells identified tumor cell states ranging from a stem-like to differentiated- phenotype that were also associated with differences in chromatin accessibility and inferred transcription factor binding activity. Analyses of chromatin accessibility resulted in the identification of ecDNA, and integrative clustering of ecDNA+ cells highlighted distinct cell states with increased copy number burden, oncogene amplification, and differential chromatin accessibility. These results suggest that a better understanding of extrachromosomal contributions to tumor diversity would aid in development of more efficient therapies.